Neuropathy of Connective Tissue Diseases and Other Systemic Diseases - Jin, Peter H.; Shin, Susan C. (Seminars in Neurology, 2019)
Peripheral neuropathy is associated with numerous systemic diseases. It is often the heralding finding, which can lead to earlier diagnoses and better outcomes. An understanding of the epidemiology and clinical features of these diseases is paramount to their diagnosis and management. This article will focus on neuropathy associated with connective tissue diseases, monoclonal gammopathies, paraneoplastic disorders, medications including chemotherapeutic agents, nutritional deficiencies, alcohol, and toxins.
Keywords: systemic disease; peripheral neuropathy; chemotherapy; nutrition; toxins